The secret daughter - Rimmer, Kelly (Forever, 2019)
"You were adopted'. Three short words and Sabina's life fractures. There would forever be a Before those words, and an After. Pregnant with her own child, Sabina can't understand how a mother could abandon her daughter, or why her parents have kept the past a secret. Determined to find the woman who gave her away, what she discovers will change everything, not just for Sabina, but for the women who have loved her all these years."--Back cover.